On possibility of star formation triggered by multiple supernovae in dwarf galaxies - Vasiliev, Evgenii O.; Shchekinov, Yu. A.; Koval’, V. V.; Egorov, Oleg (Astrophysical bulletin, 2022)
Abstract—Superbubbles driven by supernovae explosions are sometimes considered as a source of triggering star formation. Using three dimensional simulations we consider the dynamics and stability of a gas layer between interacting bubbles of different age located in the galaxy disk midplane. It is shown that the lifetime of a dense gas layer increases for the interacting bubbles formed by supernovae explosions when the separation between the clusters is larger than the scale height of the disc. In case of interacting young bubbles a dense “wall” between them is rapidly destroyed by shock waves coming from hot interiors. It was found that dense gas “survives” at the edges of the interacting layer and its mass gradually increases. The possibility of star formation at the edges of the layer is discussed and compared with observations of star formation regions in nearby dwarf galaxies.
Gesehen am 29.08.2022